Assessment of prescribing pattern based on WHO indicators at “X” Primary Health Care in Sleman Regency - Kristy Tri Wardhani; Dian Medisa; Saepudin Saepudin; Ifada Ifada (Jurnal Ilmiah Farmasi, 2022)
Abstract Background: Puskesmas is a primary level of health service facility that must implement rational drug use. A rational prescribing pattern will improve the quality of health services.Objective: The aim of this study was to know the prescribing pattern at the "X" Primary Health Care in Sleman Regency based on WHO indicators.Method: A retrospective observational study was conducted to assess the prescribing pattern. The sample was selected using simple random sampling and analyzed descriptively. The data was collected from prescriptions in Mei 2019.Result: The results of this study showed the average number of drugs per prescription was 2.66, drugs prescribed by generic name was 100%. The percentage of encounter in which injection and antibiotic was prescribed was 0% and 15.83% respectively. Most drugs (91.85%) were included in National Formulary.Conclusion: It can be concluded that the prescribing pattern at Puskesmas X is rational according to the target of the Ministry of Health and WHO, but it is necessary to carry out a continuous MTP (monitoring training planning) process involving related parties.Keywords: prescribing pattern, primary health care, Sleman, WHO indicatorsIntisari Latar belakang: Puskesmas adalah fasilitas pelayanan kesehatan tingkat I yang harus menerapkan penggunaan obat rasional. Pola peresepan yang rasional akan menghasilkan kualitas dalam pelayanan kesehatan masyarakat.Tujuan:  Penelitian ini bertujuan untuk mengetahui gambaran pola peresepan di Puskesmas “X” Kabupaten Sleman berdasarkan indikator peresepan WHO.Metode: Penelitian merupakan penelitian observasional secara retrospektif menggunakan resep bulan Mei 2019. Sampel resep diambil dengan metode random sampling dan data dianalisis secara deskriptif.Hasil: Hasil penelitian menunjukkan rata-rata jumlah obat per lembar resep adalah 2,66, tingkat peresepan obat dengan nama generik 100%, tingkat penggunaan antibiotik sebesar 15,83% dari total kasus, tingkat peresepan injeksi 0%, dan kesesuaian peresepan dengan Formularium Nasional 2017 sebesar 91,85%.Kesimpulan: Pola peresepan di Puskesmas X sudah rasional sesuai target Kementerian Kesehatan dan WHO, namun perlu dilakukan proses MTP (monitoring training planning) berkesinambungan melibatkan pihak terkait.Kata kunci: pola peresepan, puskesmas, Sleman, indikator WHO